PENGARUH KEPUASAN KERJA DAN BEBAN KERJA TERHADAP KINERJA BANK SYARIAH INDONESIA KECAMATAN MUARA TEMBESI KABUPATEN BATANG HARI JAMBI - Albetris, Albetris; Sumantri, Sumantri; Kurniawan, Dwi (Journal of Business Studies and Management Review, 2024)
The aim of this research is to explain the influence of job satisfaction and workload on employee performance at Bank Syariah Indonesia Muara Tembesi, Batang Hari - Jambi Regency. The method used is a quantitative method using multiple linear regression analysis tools, testing the significance of the influence of the variables job satisfaction (X1) and workload (X2) as independent variables and employee performance (Y) as the dependent variable using the t test and F test. The test results on the influence of the job satisfaction variable (X1) on employee performance (Y) obtained a calculated T value of 2.286> T table 1.689572. So based on the comparison of T count and T table, this means that job satisfaction has a significant effect on employee performance. The test results on the influence of the workload variable (X2) on employee performance (Y) obtained a calculated T value of 2.286 > T table 1.689572. Based on the comparison of T count and T table, this means that workload has a significant effect on employee performance. The test results on the influence of job satisfaction and workload on employee performance obtained a calculated F value of 11.649 > F table 3.27 with a significance level of 0.05, so it is proven that there is a joint and significant influence of job satisfaction and workload on employee performance. The determination test shows that the combination of job satisfaction and workload variables together contributes 49.4%. on employee performance while the remaining 50.6%) is the contribution of other variables not examined in this research.